2014
DOI: 10.1007/s00247-014-2953-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective pilot study: Can the biliary tree be visualized in children younger than 3 months on Magnetic Resonance Cholangiopancreatography?

Abstract: The complete normal biliary system (extrahepatic bile duct confluence included) is not consistently visualized in infants younger than 3 months old on non-enhanced MRCP. Thus the use of MRCP to exclude a diagnosis of biliary atresia is compromised at optimal time of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For 8 of our infant patients, we could not detect the main pancreatic duct with MRCP due to small size (<1 mm). Siles’ group [ 25 ] reported 16 MRCP pediatric cases of children younger than 3 months-of-age and they also identified main pancreatic ducts in 2 cases. Fitoz’s group [ 26 ] reported that young age can hinder pancreaticobiliary maljunction identification.…”
Section: Discussionmentioning
confidence: 99%
“…For 8 of our infant patients, we could not detect the main pancreatic duct with MRCP due to small size (<1 mm). Siles’ group [ 25 ] reported 16 MRCP pediatric cases of children younger than 3 months-of-age and they also identified main pancreatic ducts in 2 cases. Fitoz’s group [ 26 ] reported that young age can hinder pancreaticobiliary maljunction identification.…”
Section: Discussionmentioning
confidence: 99%
“…ESGE recommend endotherapy as a first-line therapy for CP in children starting at 8 years in the same conditions as in adults [215]. Two recently published large series [216,217] In the setting of neonatal anatomy, and in particular, the minute structures of biliary hypoplasia or atresia (BA), MRCP still appears to have unsatisfactory diagnostic accuracy (70% in a recent series on 190 infants) [219]. As the diagnosis of BA at MRCP is based on the absence of visualization of the extrahepatic bile ducts and a prospective evaluation [220] of normal infants by MRCP visualized extrahepatic bile ducts in 62.5% of the cases, the authors concluded that MRCP led to a high level of false positivity in the setting of neonatal cholestasis.…”
Section: Esge/espghan Recommend That Therapeutic Ercp In Pediatric Pamentioning
confidence: 99%
“…MR cholangiopancreatography (MRCP) should be included in examinations performed to evaluate biliary anomalies, by using volumetric three-dimensional heavily T2-weighted sequences performed with respiratory triggering. Noncontrast MRCP is not diagnostically reliable in this age group to evaluate BA (10). However, increasing awareness of gadolinium deposition in the central nervous system along with Elastography, which is used to assess the stiffness of the liver as a measure of fibrosis, has been recognized as a potentially useful way to distinguish between BA and hepatitis.…”
Section: Cholestatic Diseasementioning
confidence: 99%